Energy performance of passive shading and thermal insulation in multistory hotel building under different outdoor climates and geographic locations. (May 2023) - Alhuwayil, Waleed Khalid; Almaziad, Faris Abdullah; Abdul Mujeebu, Muhammad
Abstract: Though energy-efficient envelope is extensively studied, there is lack of attention on incorporating appropriate passive design strategies at the design-phase of a building in a specific climate and geographic location. This study has focused on the effect of outdoor climate and geographic location on the energy-saving potential of passive shading and thermal insulation for multistory hotel building in the northern hemisphere. The building was modelled and simulated by using DesignBuilder (Version 4.5.0.148). The cities were selected in such a manner that they represent warm, moderately hot, hot, and very hot outdoor climates but different geographic locations (according to Koppen category). The proposed shading strategy was featured by the combination of solar shading devices and self-shading. As an alternative option, the envelope was provided with high-performance insulation and glazing without solar shading. The results indicated that the outdoor climate and geographic location had significant influence on the energy-saving potential of both the options; the factors identified through sensitivity analysis were cooling degree days above the cooling setpoint (CDD-base STC ), share of cooling and heating energy demands, global horizontal irradiance, and solar shading effectiveness. For instance, Khamis Mushait and Athens cities have warm outdoor climate, but they represent different geographic locations; therefore, the building's cooling energy demands in these cities were significantly different (98% and 52% respectively of the total energy demand). Accordingly, the energy saving potential of passive solar shading was maximum (65.2%) for Khamis Mushait, while it was minimum (13.1%) for Athens. Conversely, the saving by high-performance insulation ranged from −11.6% in Khamis Mushait to a maximum of only 8.5% in Athens, which is consistent with their heating demands (2% and 48% respectively).